ANALISIS PENGARUH BRAND CHARACTERISTIC DAN EMOTIONAL BRANDING TERHADAP KEPUTUSAN PEMBELIAN DI PENTOL NONA BENGKULU - Ramadan, Muhammad Fajar; Hidayati, Arifah; Lakoni, Idham (STMIK Pringsewu, 2024)
To find out how much influence physical evidence has on impulse buying. To find out the influence of brand characteristics on purchasing decisions at Pentol Nona Bengkulu, to find out the influence of emotional branding on purchasing decisions at Pentol Nona Bengkulu, to find out the influence of brand characteristics and emotional branding on purchasing decisions at Pentol Nona Bengkulu. This research method is exploratory. Exploratory research, or also called exploratory research, is a research approach that aims to find information about a topic/problem that is not yet fully understood by a researcher. Exploratory research does not require a specific hypothesis or theory. The researcher only prepared several questions as a guide to obtain primary data in the form of information, information, as the initial data needed. Based on the results, there is an influence of brand characteristic (X1) on the purchasing decision (Y) of Nona Pentol with a value of tsig α (0.000 0.05) and the value of tcount ttable (5.749 1.65882) thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X1 has a positive effect on purchasing decisions (Y). There is an influence of emotional branding (X2) on the purchase decision (Y) of Pentol Nona with a value of tsig α (0.000 0.05) and a value of tcount ttable (4.346 1.65882), thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 has a positive effect on purchasing decisions (Y). The value of Fsig α 0.05 and Fcount F table (9.4873.08) so it can be concluded that together the independent variables have a positive effect on the dependent variable.